Heart-type fatty acid binding protein (H-FABP) as a biomarker for acute myocardial injury and long-term post-ischemic prognosis - YE Xiao-dong; HE Yi; WANG Sheng; WONG Gordon T; IRWIN Michael G; XIA Zhengyuan (Acta Pharmacologica Sinica, 2018)
Acute myocardial infarction (AMI) is a life-threatening event. Even with timely treatment, acute ischemic myocardial injury and ensuing ischemia reperfusion injury (IRI) can still be difficult issues to tackle. Apart from radiological and other auxiliary examinations, laboratory tests of applicable cardiac biomarkers are also necessary for early diagnosis and close monitoring of this disorder. Heart-type fatty acid binding protein (H-FABP), which mainly exists inside cardiomyocytes, has recently emerged as a potentially promising biomarker for myocardial injury. In this review we discuss the sensitivity and specificity of H-FABP in the assessment of myocardial injury and IRI, especially in the early stage, and its long-term prognostic value in comparison with other commonly used cardiac biomarkers, including myoglobin (Mb), cardiac troponin I (cTnI), creatine kinase MB (CK-MB), C-reactive protein (CRP), glycogen phosphorylase isoenzyme BB (GPBB), and high-sensitivity cardiac troponin T (hs-cTnT). The potential and value of combined application of H-FABP with other biomarkers are also discussed. Finally, the prospect of H-FABP is summarized; several technical issues are discussed to facilitate wider application of H-FABP in clinical practice.